IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KEGIATAN PEMBELAJARAN TEMATIK KELAS IV di SD PAB 20 BANDAR KLIPPA - Chairunnisa (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2022)
This research is motivated by various problems, including: teacher constraints in implementing character education through thematic learning, these obstacles are caused by family factors, causing character culture to decline and bullying occurs which causes academic success to also decrease. This research is a field research, in this case the researcher uses a qualitative descriptive type of research, namely presenting facts systematically so that it can be easier to understand and conclude. The purpose of this study is to determine the implementation of character education through thematic learning activities, and the obstacles faced by teachers in implementing character education, the causes of character culture can decrease which can cause academic success to also decline. The researcher uses observation and interview data collection techniques. Observations and interviews were aimed at teachers to find out how to implement character education through fourth grade thematic learning activities at SD PAB 20 Bandar Klippa. The results of the study indicate that the implementation of character education through thematic learning activities in grade IV SD PAB 20 Bandar Klippa has achieved satisfactory results. This is evidenced by the results of interviews and data analysis at the time of observation of the teacher's observation assessment with a percentage score of 65%. Teachers have been maximal in implementing character education through thematic learning activities with spontaneous activities, being friendly, disciplined and able to create a conducive atmosphere.